Malposition of Cage in Minimally Invasive Oblique Lumbar Interbody Fusion - Chaiwat Kraiwattanapong; Vanlapa Arnuntasupakul; Rungthiwa Kantawan; Gun Keorochana; Thamrong Lertudomphonwanit; Pakkanut Sirijaturaporn; Methawut Thonginta (Case Reports in Orthopedics)
Introduction. Minimally invasive oblique lumbar interbody fusion is one of the novel lateral lumbar interbody fusion techniques for which the successful early results have been reported. However, new complications were increasingly reported from ongoing studies. Case Presentation. We report a case of an unusual complication of minimally invasive oblique lumbar interbody fusion associated with contralateral nerve root compression due to deep and posterior position of polyetheretherketone cage and discussion of the operating technique for repositioning polyetheretherketone cage. Conclusion. Malposition of polyetheretherketone cage can cause contralateral nerve root compression and neurological complication. The surgical technique to proper pull the polyetheretherketone cage back into the acceptable position should be considered and well prepared.